Antibiotics in Children with Pneumonia: a Review - Kurniasih, Fatimah Intan; Hanifah, Suci (Universitas Muhammadiyah Surakarta, 2025)
Pneumonia is one of the most common infections in children; at the same time, it's also a case that consumes lots of days in hospitals with antibiotics. Essentially, antibiotics are medicines that specifically combat infection produced by bacteria, turning out to be some of the important discoveries in the entire history of medicine. This review aims to analyze the types of sensitive and resistant antibiotics in the management of pneumonia in children. Antibiotic resistance is one of the most dangerous health hazards facing the global community, which has grave consequences economically. The literature search in this study is adopted from both Google Scholar and PubMed. While on Pubmed, the keyword used includes